Perancangan Sistem Informasi Pengolahan Data Persediaan Barang Berbasis Web dengan Metode Fifo pada Berkah Abadi Mart Ngipik - Murtinawaroh Murtinawaroh; Robby Andika Kusumajaya; Agus Priyadi (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The Inventory Information System is a computerized system designed to manage and monitor incoming and outgoing goods data, thereby facilitating informed decision-making and effective stock control. Berkah Abadi Mart is a retail and wholesale store that sells daily necessities. In managing inventory, Berkah Abadi  Mart still uses a manual system with paper-based recording. This naturally causes various problems, such as stock discrepancies and recording errors in monitoring the flow of incoming and outgoing goods. The purpose of this observation is to design a web-based inventory data processing information system using the FIFO method that can assist Berkah Abadi Mart in connecting stock data and managing incoming and outgoing goods data. The development method employed is the Research and Development (R&D) method, a research approach designed to develop and produce new products or enhance existing ones through a systematic and tested research process. The result of this study is a system that can be accessed by authorized users to facilitate the inventory management process.